Detection of TP53 R249 Mutation in Iranian Patients with Pancreatic Cancer. (30th December 2013) - Mohamadkhani, Ashraf; Naderi, Elnaz; Sharafkhah, Maryam; Fazli, Hamid Reza; Moradzadeh, Malihe; Pourshams, Akram
Abstract : The TP53 gene encodes tumor protein p53 which play a major role in the etiology of pancreatic cancer. The important role of codon 249 of TP53 for binding of p53 to its sequence-specific consensus site in DNA has been revealed by crystallography's studies, and mutation at this codon was detected in the plasma of some human cancers. The TP53 Mut assessor software within the International Agency for Research on Cancer (IARC) TP53 Database was performed to evaluate every possible mutation at codon 249. DNA was extracted from the plasma of 133 pancreatic cancer patients and 85 noncancer-bearing individuals. Exon 7 in TP53 was amplified, and mutation at R249 was identified by the endonuclease cleavage of HaeIII. The group of patients showed a frequency of 11% (22 of 133 samples) R249 mutation compared to 3.5% (3 of 85 samples) in the group of control which was significant (P = 0.03 ). This mutation demonstrated statistically significant association with pancreatic cancer risk in unadjusted odds ratio (OR: 3.74, 95% CI: 1.1–13.2; P = 0.041 ); however when adjusted for confounding factors, it was marginally significant because of lower control samples. These findings demonstrate that mutation at R249 of TP53 can be considered for increasing risk of pancreatic cancer that needs more research.